Strategic marketing plan for fin-tech startup “CP&B” - Bachukin, Dmitrii (2021)
The main aim of this Master's thesis is to prepare the strategic marketing planning for a CP&B startup. Theoretical part was prepared to have the base for the practical part in order to accomplish the main aim. Marketing audit methodologies were applied, and quantitative PESTEL analysis results show that the social factors have the highest weight of importance. Also, there are four direct competitors, and the strongest are Dluhopisy.cz and Dluhopisomat. In case of the SWOT analysis. In case of the segmentation, it was decided to target millennials and the representatives from the Generation Z. The market penetration and product differentiation were decided as main strategies. The promotion tactics were proposed including the communication plan. All costs for marketing program realisation were calculated. The tools for control and monitoring were analysed specifying the metrics and targets.